Identification of novel biomarkers for adult-onset-immunodeficiency (AOID) syndrome using serum proteomics - Jeerang Wongtrakul (2018)
© 2017 Hainan Medical University Objective To identify the candidate protein biomarkers of adult-onset-immunodeficiency (AOID) syndrome using serum proteomics. Methods Screening and verification phases were performed in the study. A total of 97 serum samples were classified into three groups: AOID patients with opportunistic infections (active AOID), AOID patients without opportunistic infections (inactive AOID), and healthy control. In the screening phase, pooled sera collected from patients and healthy control in each group were separated by 2D-gel electrophoresis, analyzed for differentially expressed proteins and identified for biomarkers using LC/MS. In the verification phase, the protein candidates were selected for confirmation by western blotting. Results The analysis revealed 35 differentially expressed proteins. Three proteins including haptoglobin, gelsolin, and transthyretin, were selected for verification. The r esults showed that the levels of haptoglobin in both active and inactive AOID groups were significantly higher than that in the control group, while the levels of gelsolin in the active AOID group were significantly lower than that in the inactive AOID group. The level of transthyretin in the active AOID group was also significantly lower than that in the control group. Conclusions The comparison of serum proteins between the three groups revealed three candidates which are related to chronic inflammatory diseases. Haptoglobin and transthyretin biomarkers could be applied in clinical assessment for monitor of disease outcome, including for the study of AOID pathogenesis.